Thermal technologies in food processing (Woodhead, 2001)
Thermal technologies are traditionally a compromise between their enhancement of sensory characteristics and preservation, and their shortcomings, for example in reducing factors such as nutritional properties. The need to maximize process efficiency and final product quality has led to a number of new developments, including refinements in existing technologies and the emergence of new "minimal" techniques. Thermal Technologies in Food Processing reviews all these key developments and looks at future trends, providing an invaluable resource for all food processors (Publisher description)